PTU-076 Is faecal calprotectin (FC) a reliable marker of isolated small bowel crohn's disease (CD) activity?. (22nd June 2015) - Warner, BD; Johnston, EL; Ward, MG; Irving, PM
Abstract : Introduction: The measurement of FC is considered an important investigation in both the diagnosis and assessment of activity in CD. However, it's accuracy in isolated small bowel disease (Montreal classification L1) compared to colonic (L2) and ileocolonic (L3) remains undetermined. This study aims to establish whether FC can be used to assess disease activity in L1 disease with the same degree of confidence as with other disease locations. Method: 197 patients were selected from our biologics cohort. All patients had FC measured at the same time as C-Reactive Protein (CRP) and Harvey Bradshaw Index (HBI) were documented. Statistical analysis was done using SPSS version 22. FC (units of IU/ml) for comparisons underwent Log10 transformation. Significances between means were obtained using independent 2 sample t-test and the oneway ANOVA test. Results: Patients were divided according to Montreal classification; L1 (n = 28), L2 (n = 59) and L3 (n = 108). Mean FC for the 3 groups were 344 (median = 100), 379 (median = 80) and 288 (median = 71) respectively (P = 0.728). Comparison of mean FC was made between patients with active disease (mean FC = 543) and inactive disease (mean FC = 216); the difference was statistically significant (P < 0.015). Active disease was defined as HBI ≥5 and/or CRP >5. The table above shows the significance of the relationship between mean FC and disease activity for the 3 disease locations. Conclusion: We show that, as previously established, FC is a good marker of disease activity when compared against HBI and CRP. However in L1 disease there was no significant difference in the FC of patients with active versus inactive disease. Therefore, we conclude that disease activity cannot be determined by FC alone in isolated small bowel disease. Disclosure of interest: B. Warner: None Declared, E. Johnston: None Declared, M. Ward: None Declared, P. Irving Speaker Bureau of: AbbVie, MSD, Takeda, Warner Chilcott, Shire, Ferring and Tillotts Pharma.